On the division of labor in the maintenance of intersubjectivity: insights from the study of other-initiated repair in Vietnamese - Sidnell, Jack; Vũ, Hương Thị Thanh (Frontiers in Sociology, 2024)
Few ideas have figured more centrally in the history of social theory than that of the division of labour. Here we ask whether conversational interaction, like other forms of social activity, exhibits a division of labor and, if so, what functions this serves and how it might be understood in relation to the theories of Marx and Durkheim. We begin by noting that, though conversational participants actively work to achieve and sustain understanding, much of the time this work is invisible and only its products are displayed in the form of sequentially fitted next turns at talk. However, in sequences of other-initiated repair, the work involved in the maintenance of intersubjectivity rises to the surface. On these occasions, we can see and thus describe what participants do to achieve and sustain what they take to be adequate understanding. In our data, which consist of video recordings of casual conversations among Vietnamese same-generation peers, participants continuously display an orientation to relations of relative seniority through the selection of terms used to accomplish interlocutor reference. This pervasive orientation is also reflected in practices of repair initiation. Specifically, seniors regularly initiate repair with so-called "open class" forms such as "huh?" "ha?" which display a minimal grasp of the talk targeted, require little effort to produce and, at the same time, push responsibility for resolving the problem onto the trouble source speaker (i.e., the junior member of the dyad). In contrast, juniors often initiate repair of a senior participant's talk by displaying a detailed understanding of what has been said, either in the form of a repeat or a reformulation, and inviting the senior to confirm. We suggest then that this asymmetry in the distribution of initiation practices reflects a "division of intersubjective labor". We conclude with some thoughts on the theoretical implications of our findings and relate them not only to the theories of Marx and Durkheim but also to the writings of feminist sociolinguists who sought to describe the way in which women seem to be burdened more than men with what Pamela Fishman (1977, 1978) called "interactional shitwork.